2019
DOI: 10.1002/jgh3.12173
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for colorectal cancer and chemoprevention in ulcerative and Crohn's colitis: The need for clinical strategies to increase effectiveness

Abstract: This review considers why current strategies for surveillance and the prevention of colorectal cancer as a long‐term complication are ineffective. The role of endoscopists, pathologists, and patients are investigated. Colorectal cancer is linked to poor compliance with therapy, and attention may be better directed at improving adherence to treatment than strengthening current surveillance programs. Clearly, 5‐ASA compounds, particularly mesalazine, are the most appropriate agents to choose, but there may also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…CRC is a major long-term serious complication in patients with UC (22)(23)(24). Previous studies have shown that the main area of colon cancer incidence (25,26). Although recent studies have suggested that patients with UC do not have a particularly high rate of CRC conversion, the prevalence is still very high compared with the general population (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…CRC is a major long-term serious complication in patients with UC (22)(23)(24). Previous studies have shown that the main area of colon cancer incidence (25,26). Although recent studies have suggested that patients with UC do not have a particularly high rate of CRC conversion, the prevalence is still very high compared with the general population (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Patients must be educated about the link between IBD and CRC, which is essential to guarantee adherence to treatment and surveillance protocols. In a study of 156 patients with colitis, only 50% were aware of the correlation between their disease and CRC [28,29]. Unfortunately, surveillance endoscopies are still not offered to all high-risk patients as recommended by the guidelines.…”
Section: Discussionmentioning
confidence: 99%